Ethics and integrity in health and life sciences research - Koporc, Zvonimir (Bingley, U.K. : Emerald Publishing Limited, 2018)
Life and health sciences and biomedical studies have developed rapidly over the last few decades raising previously unanticipated ethical concerns and questions. New and emerging technologies require novel approaches, protocols and raised awareness to ensure adequate levels of biosecurity and biosafety as well as the implementation of special measures to prevent their potential misuse or dual use.This volume brings together an international collection of prominent ethics experts in health and life sciences, with the aim of providing clear and comprehensive guidelines for the establishment of efficient ethical strategies related to current and emerging biotechnologies and health research.Important current topics in research ethics including CRISPR-Cas9 technologies, gene editing, 'big data' in healthcare and life sciences, nutrition in medicine among other topics have found their place in this volume. In addition, the volume discusses the prospects for the implementation of an international unification of ethical standards in life sciences.
Prelims -- Introduction: research production in life sciences -- Promoting equity and preventing exploitation in international research: the aims, work, and output of the TRUST project -- Ebola virus disease: a lesson in science and ethics -- Ethics challenges in the digital era: focus on medical research -- Big data in healthcare and the life sciences -- Shaping a culture of safety and security in research on emerging technologies: time to move beyond "simple compliance" ethics -- Governing gene editing in the European Union: Legal and ethical considerations -- ARRIGE: toward a responsible use of genome editing -- Dual use in neuroscientific and neurotechnological research: a need for ethical address and guidance -- Ethical challenges of informed consent, decision-making capacity, and vulnerability in clinical dementia research -- Diet therapy effective treatment but also ethical and moral responsibility -- The mismatch of nutrition and "medical practice": the wayward science of nutrition in human health -- Index.
Includes index.
Print version record
Keywords: Medical ethics; Clinical medicine -- Research -- Moral and ethical aspects; Medical -- Ethics; Medical sociology